Comparison of Fiscal Policy Cyclicality Models in Foreign Countries - M. O. Kakaulina; S. E. Demidova (Финансы: теория и практика, 2025)
The article is devoted to the issues of fiscal policy cyclicality in foreign countries. The purpose of the article is to explore the features of the fiscal policy cyclicality of some federal countries - representatives of the “group of twenty” for the period from 1971 to 2022. The objective predetermined the setting of the following tasks: to analyze the cyclicality of fiscal policy by expenditures, to analyze the cyclicality of tax policy, as well as to compare the obtained results to identify common patterns of cyclicality for countries with a similar level of economic development. The study of fiscal policy cyclicality is relevant because it allows governments to adjust their fiscal policies according to the current state of the economy. This helps to smooth out fluctuations in economic activity and reduce the risk of recessions. Research methods - econometric modeling (building a linear regression model and using pooled binary least squares estimation), comparison, analysis. Main results of the study: the procyclicality of the public expenditure policy is confirmed in all the countries studied over the period considered, and it has an inverse dependence on the level of economic development of the country (the higher the level of development of the country in the period considered, the less procyclical its expenditure policy). The fiscal policy of all countries under consideration is countercyclical in terms of VAT, corporate and individual income taxes, but the degree of countercyclicality is different everywhere. The novelty of the study is the construction of a dynamic model without a free term, as well as the inclusion in the analysis of periods of global financial crisis, pandemic, the current stage of technological mode change and geopolitical bifurcation. The practical significance of the study lies in the possibility of balanced development of territories: in federal countries, where there are different levels of economic activity and income in different regions, the establishment of the type of cyclicality of fiscal policy allows a more even distribution of tax and budgetary resources to support the sustainable development of all regions.